2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6317602
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of different hole sizes on mechanical strength of wafers for back contact solar cells

Abstract: -Drilling process on wafers to produce EWT or MWT solar cells is a critical fabrication step, which affects on their mechanical stability. The amount of damage introduced during drilling process depends on the density of holes, their size and the chemical process applied afterwards. To quantify the relation between size of the holes and reduction of mechanical strength, several sets of wafers have been prepared, with different hole diameter. The mechanical strength of these sets has been measured by the ring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…This is because, the distribution of microcracks in the cells, resulting from the wafer cutting process [11 -13] and subsequent damage-etch treatments [14,15] dictates the fracture strength of the cells. Later processes like handling, screen printing, firing, soldering, and lamination induce residual stresses but need not necessarily cause microcracks (< 1 mm long) [49]. However, we do agree that the residual stresses could go to higher magnitudes, in the case of the poorly controlled processes (e.g.…”
Section: Effect Of Residual Stresses On the Fracture Strength Of Cellsmentioning
confidence: 56%
See 1 more Smart Citation
“…This is because, the distribution of microcracks in the cells, resulting from the wafer cutting process [11 -13] and subsequent damage-etch treatments [14,15] dictates the fracture strength of the cells. Later processes like handling, screen printing, firing, soldering, and lamination induce residual stresses but need not necessarily cause microcracks (< 1 mm long) [49]. However, we do agree that the residual stresses could go to higher magnitudes, in the case of the poorly controlled processes (e.g.…”
Section: Effect Of Residual Stresses On the Fracture Strength Of Cellsmentioning
confidence: 56%
“…In these samples, the localized residual bending stresses due to soldering induced deformation and subsequent flattening of the cell are absent, as we used unsoldered cells. This test clearly indicates that the soldering and lamination induced localized residual stresses in the cells significantly reduce the cell fracture strength [49,50]. This is because, the distribution of microcracks in the cells, resulting from the wafer cutting process [11 -13] and subsequent damage-etch treatments [14,15] dictates the fracture strength of the cells.…”
Section: Effect Of Residual Stresses On the Fracture Strength Of Cellsmentioning
confidence: 98%
“…However, material removal or chipping in the LASS process generates long microcracks inside the wafers, which degrades their mechanical strength and constitutes a major hurdle in further reducing the wafer thickness in LASS. [10][11][12][13] Blake et al 14) proposed the advantage of cutting brittle material (such as Si crystals) in the ductile mode, showing that the removal or chipping of material in this mode reduces wafer breakage and makes it possible to saw thinner wafers. 15,16) Several previous studies on Si crystals showed that applying sufficient hydrostatic pressure or scratching= indenting the surface and subsurface layers of Si allows the transition from elastic to plastic mode (ductile mode).…”
Section: Introductionmentioning
confidence: 99%
“…Las células EWT presentan un gran número de agujeros (del orden de 100 agujeros/cm 2 , Figura 8.2) que actúan como concentradores de tensiones provocando una considerable reducción de la resistencia de las obleas. Por ello, desde un punto de vista mecánico, estas obleas de silicio presentan un gran interés apareciendo recientemente diversos estudios acerca de la determinación de las propiedades mecánicas de obleas de este tipo ( [24], [77], [31]). 1.…”
Section: Célula Emitter Wrap Through (Ewt)unclassified
“…Estas 2 constantes deniendo el comportamiento elástico de materiales isótropos pueden ser, por ejemplo, el módulo de elasticidad o módulo de Young E y el coeciente de Poisson ν (A.23) o las constantes de Lamé λ y G(A. 24).…”
unclassified